Electromagnetic radiation amplification by means of a driven two-level system damped by broadband squeezed vacuum reservoir. (June 2020) - Bogolyubov Jr, N N; Soldatov, A V
Abstract: It is shown that a two-level quantum system with broken inversion symmetry possessing dipole moment operator with permanent non-equal diagonal matrix elements, driven by external semiclassical monochromatic high-frequency electromagnetic (laser) field and damped by broadband squeezed vacuum reservoir can amplify or absorb weak probe electromagnetic radiation field of much lower frequency depending on the reference phase of the squeezed field. Varying the degree of squeezing allows to alter the magnitude of the absorption or amplification rate.